PENGARUH HARGA DAN JENIS MEDIA PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA E-COMMERCE SHOPEE DI KABUPATEN LEBAK - Zakiyya Tunnufus; Astri Wulandari (The Asia Pacific Journal Of Management Studies, 2019)
The purchase decision is one of the important things that must be considered and used as an evaluation material for the company, because the purchase decisionwill affect the level of sales which if the level of sales decreases will have an impacton the company's profit. This study aims to determine whether there is a large influence of price and type of promotional media on purchasing decisions on e-commerce shopee.The research method used is descriptive method using a quantitative approach,which explains a problem based on data in the form of numbers (statistical data). Thepopulation used in this study is consumers who have made purchases at e-commerceshopee in the Lebak Regency with a population of 2017 as many as 1,288,103, using the formula of Slovin with an error rate of 10%, the sample obtained by 100 consumers. Data collection techniques used are the list of literature reviews andonline questionnaires. Data analysis techniques used are multiple regression analysis,multiple correlation analysis, coefficient of determination, t test and f test.Based on the calculation of multiple linear regression, the equation Y = 8,714+ 0,287 + 0,568 is obtained. This can be interpreted that the constant value of thevariable value of 0.8,714 states that if the value of the price and type of promotionalmedia is a constant = 0, then the constant value for the purchase decision is 8,714%and the value of the price regression coefficient that each addition of 1 score makes the purchase decision will increased by 0.287 (28,7%) and the regression coefficient value of the type of promotional media that each addition of 1 score then the purchase decision will increase by 0.568 (56,8%). Based on the Sperman rank correlation calculation shows that the price relationship to the purchase decision has a very low relationship that is equal to 0,473 and the type of media Promotion relationship to the purchase decision has a low relationship of 0.631. And based on the coefficient of determination (R2) of 0.457. Which implies that the effect of price and type of promotional media on purchasing decisions is 45,7%. While 55,3% is influenced by other factors not examined by researchers. Based on the t test results obtained that t-count> t-table (0.008 <0.05) for the price and (0.001 <0.05) for the type of promotional media. And the level of significance <significant level (0,000 <0.05). So H0 is rejected and Ha is accepted. So there is an influence between price and type of promotional media on purchasing decisions on e-commerce shopee